House of debt: How they (and you) caused the great recession, and how we can prevent it from happening again - Mian, Atif; Sufi, Amir (Chicago The University of Chicago Press, 2015)
The Great American Recession resulted in the loss of eight million jobs between 2007 and 2009. More than four million homes were lost to foreclosures. Is it a coincidence that the United States witnessed a dramatic rise in household debt in the years before the recession$1 (Bthat the total amount of debt for American households doubled between 2000 and 2007 to $14 trillion? Definitely not. Armed with clear and powerful evidence, Atif Mian and Amir Sufi reveal in House of Debt how the Great Recession and Great Depression.s